Pengaruh Tingkat Suku Bunga Deposito Terhadap Bunga Kupon Dan Harga Obligasi - Amwila, Andi Yudha (Jurnal Ilmiah Manajemen Kesatuan, 2016)
Investing in bonds is similar to deposits in the bank. When investors buy a bond, the investor will earn interest/coupon that is fixed at regular intervals. Bonds are long-term debt that contains a promise from the issuing party to pay benefits in the form of coupons and principal debt at a specified time. As trading and investment instruments, interest coupons and bond prices is an important structure in the bond. Coupon bonds are usually fixed rate while bond prices always fluctuate according to market conditions that are influenced by supply and demand. Formations of coupon interest and bond prices are influenced by various factors such as the level of interest rates on deposits.The purpose of this study was to determine the effect of interest rates on deposits and interest coupon bonds to determine the effect of the deposit interest rate on bond prices. Metods used in this research is descriptive quantitative method. Data were processed using Microsoft SPSS Statistics Programme Software 20. The method used is the classic assumption test by performing the normality test, autocorrelation and heteroscedasticity test. And to test the hypothesis using a simple linear regressiaon analysis, the koeficient of determination and t test. It can be concluded that the deposit rate (X) has a significant influence on the bond coupon rate (Y1). Regression coefficient (b) is equal to 0.806 (zero point eight hundred and six) that indicates if the deposit rate increased by 1 unit then the coupon rate will be increased by 0.806 (zero point eight hundred and six). This suggests that the effect of the interest rate on deposits is positive or zero coupon bonds directly proportional. Deposit rate (X) has a significant influence on bond prices (Y2). Regression coefficient (b) is equal to -2.414 (minus two point four hundred and fourteen) that indicates if the deposit rate increased by 1 unit, then the price of bonds will be negative or decreased by -2.414 (minus two point four hundred and fourteen). Thus, the influence of deposit interest rate on the price of bonds is negatively or inversely.